Analysis of BPM/Pulse rate and its correlation with BMI for sprint activity using ATMega328 based Arduino Uno. (2023) - Sharma, Divya; Jain, Rohan Kumar; Sharma, Ritu; Shan, B. Priestly; Shiney, O. Jeba
Abstract: In this paper, an attempt has been made to study the time required for a subject to return back to the normal state after excitation of the subject through sprint activity. The excited levels are correlated with body mass index (BMI), and age of the subject. A data collection device for the same has been developed using ATmega328 based Arduino Uno micro-controller. A total of 50 subject of age groups varying from 11 to 40 years have been involved in the study, the sprint activity was recorded for one-minute duration. The subject's data was recorded 1) Before start of sprint 2) 30 to 60 s after sprint 3) Time at which the subject vital parameters come down to normal state. From the analysis, it can be found that subjects with BMI less than 18.5 and with BMI above 24.9 took more time to return back to the rest.